A new genus of Sabellidae (Annelida, Polychaeta) from Antarctica, with discussion of relationships among plesiomorphic genera within Sabellinae - Licciano, Margherita; Giangrande, Adriana; Gambi, Maria Cristina (Zootaxa, 2009)
A new genus of Sabellidae (Annelida, Polychaeta), collected in the soft bottoms off the Antarctic Peninsula (Antarctica) in January 2006 is described. The new genus Euchoneira is included in the most plesiomorphic area in the sub-family Sabellinae. Similar to the genus Euchone, this new taxon presents a well developed anal depression with lateral wings, but the shape of abdominal uncini resembles that of Jasmineira. The new species Euchoneira knoxi gen. sp. nov., very abundant in the investigated area, is a gonochoric form (sex-ratio close 1:1). Females contained eggs ranging from 100 to 250 µm in diameter (modal class 175 µm) either in the abdomen or thorax. Males with mature sperm had spermatozoa with a characteristic cylindrical shape of the nucleus with a pointed, “nip-like” acrosome, a morphology similar to that already observed in Euchone pallida Ehlers, 1908, a second species collected together with the new taxon and already known for the Antarctic area. Additions to the description of E. pallida concerning internal structure of the crown, is also given. To define the relationships between the newly described genus and the genera present in the plesiomorphic area of the Sabellinae subfamily, a cladistic analysis was performed utilizing a previous data set after adding the new taxon. The consensus tree confirmed Amphicorina armandi (Claparéde, 1868) as the most plesiomorphic taxon separated from all the others. The new genus is located in an intermediate position between Jasmineira - Claviramus and the clade containing Chone and Euchone species, close to Fabrisabella vasculosa.